Does Increasing Treatment Frequency Address Suboptimal Responses to Ivermectin for the Control and Elimination of River Blindness?. (21st March 2016) - Frempong, Kwadwo K.; Walker, Martin; Cheke, Robert A.; Tetevi, Edward Jenner; Gyan, Ernest Tawiah; Owusu, Ebenezer O.; Wilson, Michael D.; Boakye, Daniel A.; Taylor, Mark J.; Biritwum, Nana-Kwadwo; Osei-Atweneboana, Mike; Basáñez, María-Gloria
Abstract : The first 3 years of biannual ivermectin distribution in Ghana have substantially reduced Onchocerca volvulus infection levels in 10 sentinel communities, but longitudinal analysis indicates that some communities are still consistently responding suboptimally to treatment, with implications for onchocerciasis elimination. Abstract: Background. Several African countries have adopted a biannual ivermectin distribution strategy in some foci to control and eliminate onchocerciasis. In 2010, the Ghana Health Service started biannual distribution to combat transmission hotspots and suboptimal responses to treatment. We assessed the epidemiological impact of the first 3 years of this strategy and quantified responses to ivermectin over 2 consecutive rounds of treatment in 10 sentinel communities. Methods. We evaluated Onchocerca volvulus community microfilarial intensity and prevalence in persons aged ≥20 years before the first, second, and fifth (or sixth) biannual treatment rounds using skin snip data from 956 participants. We used longitudinal regression modeling to estimate rates of microfilarial repopulation of the skin in a cohort of 217 participants who were followed up over the first 2 rounds of biannual treatment. Results. Biannual treatment has had a positive impact, with substantial reductions in infection intensity after 4 or 5 rounds in most communities. We identified 3 communities—all having been previously recognized as responding suboptimally to ivermectin—with statistically significantly high microfilarial repopulation rates. We did not find any clear association between microfilarial repopulation rate and the number of years of prior intervention, coverage, or the community level of infection. Conclusions. The strategy of biannual ivermectin treatment in Ghana has reduced O. volvulus microfilarial intensity and prevalence, but suboptimal responses to treatment remain evident in a number of previously and consistently implicated communities. Whether increasing the frequency of treatment will be sufficient to meet the World Health Organization's 2020 elimination goals remains uncertain.